Effectiveness, quality of life, and safety of secukinumab versus conventional systemic therapy in patients with erythrodermic psoriasis: a comparative study - Zhou, Ying; Chen, Weiquan; Fang, Linglu; Qiu, Fang; Wu, Jiayuan; Li, Jing (Frontiers in Medicine, 2024)
Abstract Background: Erythrodermic psoriasis (EP) is a rare but life-threatening variant of psoriasis less responsive to conventional systemic therapies (CST). Limited research exists on the management of EP with secukinumab. Objectives: To compare the effectiveness, quality-of-life effects and safety of secukinumab versus CST in patients with EP. Methods: EP patients treated with either secukinumab or CST between August 2020 and October 2022 were identified using the National Clinical Research Center for Dermatologic and Immunologic Diseases (NCRC-DID) database encompassing 962 healthcare organizations. Propensity score matching (PSM) was performed to balance the cohorts based on demographic and clinical characteristics. The primary outcomes assessed were Psoriasis Area and Severity Index (PASI), Body Surface Area (BSA), and Dermatology Life Quality Index (DLQI) scales at 4 weeks, 10-14 weeks, and 22-24 weeks. Results: The study included 311 patients (160 receiving eculizumab and 151 receiving CST), among them, 101 matched pairs were generated by propensity score matching (PSM). Eculizumabs recipients displayed a notably accelerated response compared to those receiving CST, evidenced by significantly higher rates of achieving PASI50 (before PSM: 73.8% vs. 61.6%, after PSM: 76.2% vs. 63.4%), PASI90 (before PSM: 36.9% vs. 25.8%, after PSM: 40.6% vs. 25.7%), and BSA50(before PSM: 64.4% vs. 50.3%, after PSM: 68.3% vs. 51.5%) at week 4 (P<0.05). However, before PSM, secukinumab showed significantly higher DLQI0/1 rates at weeks 4 (41.3% vs. 29.8%) and 12 (63.8% vs. 44.8%). After PSM, statistically significant differences were observed at week 12 for PASI and BSA scores, and at week 4 for DLQI scores (P<0.05). Similar efficacy trends were observed in other outcomes at week 0 up to week 24, but no statistical differences were noted. Conclusions: Compared to the CST, secukinumab tend to offer a more rapid response and achieve greater improvements in clinical symptoms and quality of life for EP patients.